2014
DOI: 10.3174/ajnr.a3847
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Alzheimer Disease Pathology

Abstract: Development of molecular imaging agents for fibrillar β–amyloid (Aβ) positron emission tomography (PET) during the last decade brought molecular imaging of Alzheimer’s disease (AD) pathology into the spotlight. Large cohort studies with longitudinal follow-up in cognitively normal, mild cognitive impairment and AD patients indicate that Aβ deposition can be detected many years before the onset of symptoms with molecular imaging and its progression can be followed longitudinally. The utility of Aβ PET in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…AD can lead to cognitive decline, memory loss, language problems, and the deterioration of executive function. The inflammatory response to the extracellular A β -containing plaques is central to this disease ( Kantarci, 2014 ;Morales et al, 2014 ;Sorrentino et al, 2014 ). Microglia play a key role in the inflammation response and are usually found around senile plaques in the brains of AD patients.…”
Section: Tlr/myd88 Signaling and Admentioning
confidence: 99%
“…AD can lead to cognitive decline, memory loss, language problems, and the deterioration of executive function. The inflammatory response to the extracellular A β -containing plaques is central to this disease ( Kantarci, 2014 ;Morales et al, 2014 ;Sorrentino et al, 2014 ). Microglia play a key role in the inflammation response and are usually found around senile plaques in the brains of AD patients.…”
Section: Tlr/myd88 Signaling and Admentioning
confidence: 99%
“…The PET imaging tracers help in differentiating dementia syndromes, which do not have overlap of the underlying pathological process. 13 The purpose of this article was to review the role of brain PET imaging in the diagnosis of AD.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…The use of Aβ-specific ligands in PET has opened new avenues for AD pathology research (reviewed by Kantarchi [67] ). Arguably one of the most important contributions of Aβ-PET imaging in recent years was empirical evidence that brain Aβ-deposition does not reside solely in the domain of AD pathology, but is also a component of brain aging [68,69] .…”
Section: Arterial Stiffness and The Brainmentioning
confidence: 99%
“…Extensive Aβ deposition precedes cognitive impairment, and is associated with APOE genotype, age and a higher risk of cognitive decline [78] . Population-based studies with Aβ-PET shows the prevalence of AD-like Aβ deposition is between 20 and 34% in cognitively normal older adults [67] and increases dramatically with increasing age [15,69] . Recently, we showed that 9th decade of life the proportion of nondemented older adults with AD-like Aβ deposition increased from 45 to 75% over 2 years of follow-up [13] .…”
Section: Arterial Stiffness and The Brainmentioning
confidence: 99%